2008
DOI: 10.3122/jabfm.2008.06.080080
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Effects on Cardiovascular Disease and its Diagnosis

Abstract: The higher prevalence of cardiovascular disease in obese individuals is indirectly mediated, to a large extent, by the increased frequency of various well known risk factors like hypertension, diabetes, and dyslipidemia, either individually or as part of the metabolic syndrome. However, there are several ways in which obesity directly affects the cardiovascular system; these will be discussed in detail. We also focus on various challenges posed by obesity in the performance and interpretation of cardiac invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 52 publications
1
57
0
17
Order By: Relevance
“…22,23 In a study, WHR showed a stronger association with lifestyle factors, such as physical inactivity, than BMI. 24 Thus, the high predictive power of WHR for incident CVD in our study population might be attributable to the high prevalence of sedentary lifestyle, especially in females.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghmentioning
confidence: 97%
“…22,23 In a study, WHR showed a stronger association with lifestyle factors, such as physical inactivity, than BMI. 24 Thus, the high predictive power of WHR for incident CVD in our study population might be attributable to the high prevalence of sedentary lifestyle, especially in females.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghmentioning
confidence: 97%
“…The role of the liver and the induction of obesity early in life are of critical understanding to the development of hyperinsulinemia which may lead to diabetes and other morbid diseases such as cancer and coronary artery disease. Visceral fat is more metabolically active than peripheral fat and is associated with Type 2 diabetes, dyslipidemia, high blood pressure, and increased risk for atherosclerotic disease [8] [9]. The waist-to-hip ratio helps identify patients with excess visceral adiposity.…”
Section: Adiposity and Obese Classificationsmentioning
confidence: 99%
“…In mice, induction of obesity has become important and the models have been created to study obesity and its co-morbidities such as Type 2 Diabetes, hypertension, hypercholesterolemia and atherosclerosis as found in man. In reports related to cardiovascular disease and threats to global health, various diets and drugs have been considered because of their ability to regulate genes linked to human adiposity that are closely linked to life extension in man [8] [9]. Early dietary intervention in obese mice models allowed reduction in the severity of visceral obesity and several chronic diseases such as NAFLD and neurodegenerative diseases [10]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread of cardiovascular disease in obese individuals is indirectly mediated by the increased frequency of certain risk factors like hyperlipidemia, diabetes, and hypertension. However, obesity directly affects the cardiovascular system in several ways) [3]. Obese patients have increased concentration of many adipokines like leptin, resistin and other chemokines like tumor necrosis factoralpha, lipoprotein lipase, plasminogen activator inhibitor1and interleukin-6.…”
Section: Introductionmentioning
confidence: 99%